Fireproof insulating paint for new energy battery and preparation method of fireproof insulating paint

By modifying the mixture of boron nitride nanosheets and mica powder, combined with end-carboxyl hyperbranched polyester and silane coupling agent treatment, the crosslinking density and dispersibility of the coating are improved, solving the problem of insufficient flexibility of the coating when the hardness is increased, and achieving high-strength and high-flexibility fire-retardant insulating coating for batteries.

CN120758106APending Publication Date: 2025-10-10SUZHOU BAIMIN ELECTRONIC MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511011902.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

While existing battery coatings have improved hardness, they lack flexibility, causing the paint film to crack when the battery casing deforms, affecting the fire resistance.

Method used

A mixture of modified boron nitride nanosheets and mica powder is used as filler. The boron nitride nanosheets are alkalized and copolymerized with terminal carboxyl hyperbranched polyester to enhance the crosslinking density and dispersibility of the coating. At the same time, the mica powder is modified with a silane coupling agent to improve the interfacial compatibility.

Benefits of technology

The strength and flexibility of the coating are improved, the overall performance of the battery coating is enhanced, and it has excellent insulation and flame retardancy, making it suitable for new energy batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005512043650000071
    Figure BDA0005512043650000071
  • Figure BDA0005512043650000081
    Figure BDA0005512043650000081
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a fireproof insulating coating for a new energy battery and a preparation method of the fireproof insulating coating. The fireproof insulating coating for the new energy battery is prepared from the following raw materials in parts by weight: 100 to 140 parts of a water-based acrylic resin raw material, 140 to 150 parts of deionized water, 0.2 to 0.4 part of a flatting agent, 45 to 55 parts of ammonium polyphosphate, 0.5 to 2 parts of a coalescing agent and 0.1 to 1 part of a de-foaming agent, the raw material of the water-based acrylic resin comprises modified boron nitride nanosheets, and the filler is the modified boron nitride nanosheets and is prepared by alkalizing boron nitride nanosheets to prepare hydroxylated boron nitride nanosheets, then grafting carboxyl-terminated hyperbranched polyester through an esterification reaction, and then carrying out an esterification reaction with hydroxypropyl methacrylate; the battery coating has the advantage that the flexibility of the battery coating is improved under the condition that the hardness of the battery coating is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of coatings, in particular to a fireproof insulating coating for new energy batteries and a preparation method thereof. BACKGROUND

[0002] The new energy automobile refers to an automobile adopting unconventional vehicle fuel as a power source and integrating advanced vehicle power control and driving technologies. The new energy automobile includes an electric automobile, which is an automobile adopting a single storage battery as a storage power source. The electric automobile drives an electric motor through the battery to provide electric energy, drives the electric motor to operate, and thus drives the automobile to travel. The lithium battery is one of important components of the electric automobile. At present, a major problem of the electric automobile is that the battery pack is damaged due to collision or extrusion, the battery catches fire and explodes, and the safety problem is very serious.

[0003] At present, the fireproof performance of the battery assembly is improved mainly by using fireproof coatings and flame-retardant battery housings. However, the insulating performance and heat conduction and heat dissipation performance of the coating are also very important for the battery. In the related art, the insulating and heat conduction performance of the coating can be effectively improved by boron nitride. However, the hardness of the boron nitride is very high, and the compatibility between the boron nitride and the coating system is insufficient, so that the toughness of the coating is low. When the battery housing is deformed, the coating film is prone to crack, and the performance of the coating is reduced. SUMMARY

[0004] In order to improve the flexibility of the coating for the battery under the condition of maintaining the hardness of the coating for the battery, the application provides a fireproof insulating coating for a new energy battery and a preparation method thereof.

[0005] In a first aspect, the application provides a fireproof insulating coating for a new energy battery, which adopts the following technical scheme: A fireproof insulating coating for a new energy battery includes the following raw materials by weight: 100-140 parts of a water-based acrylic resin raw material, 140-150 parts of deionized water, 0.2-0.4 parts of a leveling agent, 45-55 parts of ammonium polyphosphate, 0.5-2 parts of a film-forming aid, and 0.1-1 parts of a defoaming agent. The preparation method of the water-based acrylic resin raw material is as follows: Under a nitrogen atmosphere, using n-butanol as a solvent, adding 6-12 parts by weight of filler, stirring and dispersing, then adding 4-7 parts by weight of styrene, 1-4 parts by weight of methacrylic acid, 3-7 parts by weight of hydroxyethyl acrylate, 3-7 parts by weight of methyl methacrylate, and 15-25 parts by weight of butyl acrylate, stirring until dissolved, then adding 0.2-0.3 parts by weight of dibenzoyl peroxide, raising the temperature to 85-100° C., stirring and reacting; then continuously adding 12-18 parts by weight of styrene, 4-7 parts by weight of methacrylic acid, 8-12 parts by weight of hydroxyethyl acrylate, 8-12 parts by weight of methyl methacrylate, and 30-40 parts by weight of butyl acrylate, stirring until dissolved, continuously adding 0.4-0.6 parts by weight of dibenzoyl peroxide, stirring and reacting, and removing n-butanol to obtain a water-based acrylic resin raw material; The filler is a modified boron nitride nanosheet, which is prepared by alkalizing boron nitride nanosheets to obtain hydroxylated boron nitride nanosheets, then grafting end-carboxyl hyperbranched polyester through an esterification reaction, and then esterifying with hydroxypropyl methacrylate to obtain the filler.

[0006] By adopting the above technical solution, the boron nitride nanosheets are modified and alkalized to have a large number of hydroxyl groups on their surface, and then carboxyl-terminated hyperbranched polyesters are grafted by esterification, and then double-bond acrylates are grafted by esterification, and then copolymerized with monomers such as styrene and methacrylic acid, so that the hyperbranched grafted boron nitride nanosheets are cross-linked and grafted into acrylic resin, which greatly reduces the interfacial tension of the boron nitride nanosheets, and contains a large number of double-bond acrylates on its surface. After the copolymerization reaction, it can exist as a cross-linking center, thereby increasing the cross-linking density of the coating and greatly improving the strength of the coating. In addition, the present application adopts carboxyl-terminated hyperbranched polyesters. The molecular viscosity of the hyperbranched polymer is extremely low and the volume is large. After being grafted with the boron nitride nanosheets, the dispersibility of the boron nitride nanosheets is excellent. The hyperbranched polymer has a high content of double-bond molecules at the end of the side chains, which greatly reduces the interfacial energy with the coating system, can provide good flexibility of the coating, and can also improve the cross-linking of the system and improve the protective function of the coating. Taken together, the coating has a stronger integrity, thereby improving the strength of the coating and providing better flexibility.

[0007] Preferably, the average molecular weight of the carboxyl-terminated hyperbranched polyester is 2600.

[0008] By adopting the technical scheme, it is found through the exploration of the molecular weight of the carboxyl-terminated hyperbranched polyester that the overall performance of the coating is better when the molecular weight is 2600. It is guessed that when the molecular weight is low, the dispersibility of the boron nitride nanosheet is insufficient, the double bond grafting is less, and the hyperbranched molecule has a lower performance in flexibility and crosslinking; when the molecular weight is high, the molecular volume is large, and the steric hindrance of the molecular reaction is large, which affects the grafting and esterification efficiency of the hyperbranched polyester, thereby reducing the crosslinking density on the surface of the hyperbranched polyester and the performance of the coating. Therefore, the hyperbranched polyester with the above-mentioned specific molecular weight has outstanding advantages in the synthesis method and the use of the coating in the present application.

[0009] Preferably, the diameter of the boron nitride nanosheet is 0.1-0.6 μm, the thickness is 20-80 nm, and the specific surface area is 500 m 2 / g.

[0010] By adopting the technical scheme, the boron nitride nanosheet has the characteristics of small particle size and large specific surface area. After modification, it is used in the insulating coating, and the insulating property and strength of the coating are improved.

[0011] Preferably, the filler is a mixture of modified boron nitride nanosheet and mica powder, and the weight ratio of the modified boron nitride nanosheet to the mica powder is 5:(0.1-2.5).

[0012] By adopting the technical scheme, the filler is a mixture of modified boron nitride nanosheet and mica powder. The mica powder has the advantages of high electrical insulation, acid and alkali corrosion resistance, elasticity, toughness, sliding property, heat resistance, sound insulation, and small thermal expansion coefficient. Replacing a certain amount of modified boron nitride nanosheet with mica powder can maintain the strength of the coating while improving the flexibility of the coating.

[0013] Preferably, the mica powder is modified mica powder, which is prepared by reacting mica powder and a double-bond-containing silane coupling agent.

[0014] By adopting the technical scheme, the mica powder is modified by treating its surface with a double-bond-containing silane coupling agent. On the one hand, the silane coupling agent can reduce the interfacial tension. On the other hand, the double bond can participate in the copolymerization reaction; thus, the mica powder also becomes a crosslinking copolymerization center, and its dispersibility is improved. The crosslinking effect of the mica powder and the boron nitride nanosheet is synergistic, and the coating has excellent strength and flexibility.

[0015] Preferably, the double-bond-containing silane coupling agent is one or more of vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltris(butanone oxime)silane, acryloxy-methyltrimethoxysilane, 7-octenyltrimethoxysilane, and gamma-methacryloxypropyltrimethoxysilane.

[0016] More preferably, the double bond-containing silane coupling agent is vinyltriethoxysilane.

[0017] When experimenting with the selection of silanes, it was found that vinyl silanes can achieve better strength and flexibility when used in coatings after modification than 7-octenylsilane. Analysis suggests that this may be because mica powder and boron nitride nanosheets both participate in the polymerization reaction based on double bonds. The double bonds of the boron nitride nanosheets are grafted to the ends of the hyperbranched polyester. Therefore, there are large hyperbranched polyester structures in the side chains of the acrylic resin, resulting in low strength around the resin chain in the coating. Mica powder can play a complementary role. After the mica powder is modified with vinyl triethoxysilane, the chain distance between its double bonds and the mica powder is very short. Therefore, after polymerization, the mica powder tends to be distributed in the side chains of the acrylic resin close to the main chain. When both boron nitride and mica powder are grafted to the acrylic side chains, the mica powder with shorter side chains better fills the problem of missing strength around the main chain, thereby making the distribution of boron nitride and mica powder in the overall system more reasonable, synergistically achieving strength enhancement, while also ensuring good toughness.

[0018] Preferably, the particle size of the mica powder is 3000 mesh.

[0019] By adopting the above technical solution, the smaller the particle size of the mica powder, the better the comprehensive performance of the coating, but the improvement from 3000 mesh to 6000 mesh is small. Considering the comprehensive economic cost, the particle size of 3000 mesh is the best choice for production.

[0020] In a second aspect, the present application provides a method for preparing a fire-retardant insulating coating for new energy batteries, which adopts the following technical solution: A method for preparing a fireproof insulating coating for new energy batteries comprises the following steps: A water-based acrylic resin raw material, deionized water, a leveling agent, ammonium polyphosphate, a film-forming aid and a defoaming agent are stirred and mixed to obtain a fireproof insulating coating for new energy batteries.

[0021] By adopting the above technical solution, the preparation method of the present application is relatively conventional, does not require special processes or equipment modifications, has a wide adaptability to process parameters, has a high pass rate for the prepared coating, and is suitable for large-scale production.

[0022] In summary, this application includes at least one of the following beneficial technical effects: 1. By modifying boron nitride nanosheets, alkalizing them so that their surfaces are provided with a large number of hydroxyl groups, then grafting end-carboxyl hyperbranched polyesters through esterification, then grafting double-bond acrylates through esterification, and then copolymerizing with monomers such as styrene and methacrylic acid, the boron nitride nanosheets are cross-linked and grafted into acrylic resins, greatly reducing the interfacial tension of the boron nitride nanosheets, and containing a large number of double-bond acrylates on their surfaces. After copolymerization, they can exist as cross-linking centers, thereby increasing the cross-linking density of the coating and greatly improving the strength of the coating. In addition, the present application adopts end-carboxyl hyperbranched polyesters, and the molecular viscosity of the hyperbranched polymer is extremely low and the volume is relatively large. After grafting the boron nitride nanosheets, the dispersibility of the boron nitride nanosheets is excellent, and the content of double-bond molecules at the end of the branched chain of the hyperbranched polymer is high, so that the interface energy between the boron nitride nanosheets and the coating system is greatly reduced. In summary, the integrity of the coating is made stronger, thereby improving the strength of the coating and having better flexibility.

[0023] 2. By replacing the filler with a mixture of modified boron nitride nanosheets and mica powder, mica powder has the advantages of extremely high electrical insulation, acid and alkali corrosion resistance, elasticity, toughness and sliding, heat resistance and sound insulation, and small thermal expansion coefficient. Replacing a certain amount of modified boron nitride nanosheets with mica powder can maintain the strength of the coating while improving the flexibility of the coating.

[0024] 3. This application selects specific silane-modified mica powder, which demonstrates better adaptability in synergistic enhancement with hyperbranched polyester-modified boron nitride.

[0025] 4. The volume resistivity of the coating prepared in this application is (3.1-5.6)×10 14 Ω·m, the limiting oxygen index is between 29.3-35.4%, and the hardness can reach 4-6H. The flexibility is 3.62mm and below, and the lowest can reach 0.53mm. This shows that the coating of the present application has excellent insulation and flame retardancy, and its hardness and flexibility are also excellent, which is very suitable for batteries. DETAILED DESCRIPTION

[0026] The following is a further detailed description of this application in conjunction with the specific content.

[0027] raw material The raw materials of this application were all purchased from the market, wherein the deionized water was industrial deionized water; the specifications of the boron nitride nanosheets were as follows: hexagonal boron nitride nanosheets, with a diameter of 0.1-0.6 μm, a thickness of 20-80 nm, and a specific surface area of ​​500 m 2 / g; the model of the defoamer is DT-604; the model of the leveling agent is BYK346; the ammonium polyphosphate is a general-purpose grade, model LD-102; and the film-forming aid is ester alcohol dodecahydrate.

[0028] Preparation Example Preparation Example 1 A modified boron nitride nanosheet, the preparation method of which is as follows: S1. Prepare 100 mL of 4.5 mol / L sodium hydroxide solution, then add 1 g of boron nitride nanosheets, ultrasonically disperse for 10 min, heat to 80°C, stir and react for 72 h, filter, wash with water, and dry to obtain hydroxylated boron nitride nanosheets; S2. Add the hydroxylated boron nitride nanosheets of S1 to 200 mL of N,N-dimethylformamide, and after ultrasonic dispersion, add 20 g of terminal carboxyl hyperbranched polyester and stir until completely dissolved. Then, add 50 mL of toluene as a water-carrying agent and 0.1 g of p-toluenesulfonic acid as a catalyst. Heat to 160°C and stir to react for 24 hours. Continue to add 30 g of hydroxypropyl methacrylate and stir to react for 15 hours. Filter, wash, and dry to obtain modified boron nitride nanosheets; the average molecular weight of the terminal carboxyl hyperbranched polyester is 1000, and the corresponding specification model is Hyper C101.

[0029] Preparation Example 2 A modified boron nitride nanosheet is different from that of Preparation Example 1 in that the average molecular weight of its carboxyl-terminated hyperbranched polyester is 2600, and the corresponding specification model is Hyper C102.

[0030] Preparation Example 3 A modified boron nitride nanosheet is different from that of Preparation Example 1 in that the average molecular weight of its carboxyl-terminated hyperbranched polyester is 6400, and the corresponding specification model is Hyper C103.

[0031] Preparation Example 4 A modified mica powder, the preparation method of which is as follows: Add 5 g of vinyltriethoxysilane and 2 g of mica powder to 100 mL of ethanol-water solution (volume ratio of ethanol to water is 1:1), heat to 60° C., stir and react for 3 h, filter, wash, and dry to obtain modified mica powder; the mica powder is 1000 mesh muscovite powder.

[0032] Preparation Example 5 A modified mica powder is different from Preparation Example 4 in that the particle size of the muscovite powder is 3000 mesh, and the remaining steps are the same as Preparation Example 4.

[0033] Preparation Example 6 A modified mica powder is different from Preparation Example 4 in that the particle size of the muscovite powder is 6000 mesh, and the remaining steps are the same as Preparation Example 4.

[0034] Preparation Example 7 A modified mica powder is prepared in accordance with Preparation Example 4, which differs from Preparation Example 4 in that an equal amount of 7-octenyltrimethoxysilane replaces vinyltriethoxysilane, and the remaining steps are the same as those of Preparation Example 4. Example

[0035] Example 1 A fireproof insulating coating for new energy batteries, the raw materials and their respective raw materials are shown in Table 1, and the preparation method thereof is as follows: S1. Under a nitrogen atmosphere, 9 g of filler was added to 500 mL of n-butanol, and after stirring and dispersing, 6 g of styrene, 2 g of methacrylic acid, 5 g of hydroxyethyl acrylate, 5 g of methyl methacrylate and 18 g of butyl acrylate were added, and the mixture was stirred until dissolved. Then, 0.255 g of dibenzoyl peroxide was added, and the temperature was raised to 90 ° C. and stirred for 90 min; then 15 g of styrene, 6 g of methacrylic acid, 10 g of hydroxyethyl acrylate, 10 g of methyl methacrylate and 35 g of butyl acrylate were added, and after stirring until dissolved, 0.5 g of dibenzoyl peroxide was added, and the mixture was stirred for 8 h. The mixture was then concentrated under reduced pressure to remove n-butanol to obtain a water-based acrylic resin raw material; the filler was modified boron nitride nanosheets, which were prepared by the method of Preparation Example 1; S2. According to the amounts of each raw material in Table 1, the water-based acrylic resin raw material, deionized water, leveling agent, ammonium polyphosphate, film-forming aid and defoaming agent are stirred and mixed to obtain a fire-retardant insulating coating for new energy batteries.

[0036] Table 1 Raw materials and amounts of raw materials used in Example 1 (g) Water-based acrylic resin raw materials 120 Deionized water 145 Leveling agent 0.3 Ammonium polyphosphate 50 Coal-forming aids 1.5 defoaming agent 0.5 Example 2 A fireproof insulating coating for new energy batteries, which is different from Example 1 in that the modified boron nitride nanosheets in S1 are prepared by the method of Preparation Example 2, and the rest are the same as Example 1.

[0037] Example 3 A fireproof insulating coating for new energy batteries, which is different from Example 1 in that the modified boron nitride nanosheets in S1 are prepared by the method of Preparation Example 3, and the rest are the same as Example 1.

[0038] Example 4 A fire-retardant insulating coating for new energy batteries, which differs from Example 2 in that the filler in S1 is a mixture of modified boron nitride nanosheets and mica powder, the weight ratio of the modified boron nitride nanosheets to the mica powder is 5:2, the modified boron nitride nanosheets are prepared by Preparation Example 2, the mica powder is muscovite powder, and the particle size is 3000 mesh. The rest is the same as Example 2.

[0039] Example 5 A fireproof insulating coating for new energy batteries, which is different from example 4 in that the mica powder in the filler is modified mica powder, the modified mica powder is prepared by preparation example 4, and the rest is the same as example 4.

[0040] Example 6 A fireproof insulating coating for new energy batteries, which is different from example 5 in that the modified mica powder is prepared by preparation example 5, and the rest is the same as example 5.

[0041] Example 7 A fireproof insulating coating for new energy batteries, which is different from example 5 in that the modified mica powder is prepared by preparation example 6, and the rest is the same as example 5.

[0042] Example 8 A fireproof insulating coating for new energy batteries, which is different from example 5 in that the modified mica powder is prepared by preparation example 7, and the rest is the same as example 5.

[0043] Comparative example Comparative example 1 A fireproof insulating coating for new energy batteries, which is different from example 1 in that the modified boron nitride nanosheet in S1 is replaced by equal mass of hydrolyzed polymaleic anhydride with an average molecular weight of 1000 during preparation, and the rest is the same as example 1.

[0044] Comparative example 2 A fireproof insulating coating for new energy batteries, which is different from example 1 in that the filler in S1 is equal mass of boron nitride nanosheet, and the rest is the same as example 1.

[0045] Performance detection test Detection method / test method A fireproof insulating coating for new energy batteries was prepared according to the preparation method in examples 1-8 and comparative examples 1-2, and then detected according to the following detection method, and the detection results are shown in table 2.

[0046] Volume resistivity: detected according to the provisions in HG / T 3331-2012 Insulating paint film volume resistivity coefficient and surface resistivity coefficient determination method.

[0047] Hardness: refer to the judgment standard in GB 6739-86 Coating film hardness pencil determination method: after the paint film is dried, a 3cm length is drawn on the paint film at a 45° angle with a vertical pressure of 1kg, 5 times, and the paint film does not appear scratches, and the pencil level hardness is the paint film hardness.

[0048] Flexibility: According to the provisions of GB 1731-2020 Paint Film, Putty Film Flexibility Test Method, the shaft stick tester is used to test the bending of the painted tin plate on the shaft stick of different diameters, and the minimum shaft stick diameter (mm) that does not cause the paint film to be damaged after bending is used to represent the flexibility.

[0049] Limiting oxygen index: According to GB / T 2406.1-2008 method and UL-94 method, the oxygen index tester and UL-94 horizontal vertical burning test box are used to test the flame retardant performance of the coating.

[0050] Table 2 Test results of examples 1-8 and comparative examples 1-2 From the test data of examples 1-8 and comparative examples 1-2, and table 2, it can be seen that the volume resistivity of the coating prepared in the present application is between (3.1-5.6) x 10 14 Ω·m, the limiting oxygen index is between 29.3-35.4%, and the hardness can reach 4-6H, the flexibility is all below 3.62mm, and the minimum can reach 0.53mm; It shows that the coating of the present application has excellent insulation and flame retardance, and its hardness and flexibility also perform excellently, which is very suitable for batteries.

[0051] Boron nitride has good electrical insulation and thermal conductivity, and at high temperature, boron nitride shows good stability, even above 2000℃, it can still maintain its performance. Based on the various excellent properties of boron nitride, it is widely used in high-voltage high-frequency electricity and plasma arc insulators, high-temperature resistant frame coating for automatic welding, high-frequency induction furnace materials, semiconductor solid-phase doping materials, atomic reactor structural materials, neutron radiation prevention packaging materials, radar transmission window, radar antenna medium and rocket engine composition, etc. Boron nitride nanosheet has the characteristics of small particle size and large specific surface area, and when it is used in insulating coating, it is expected to improve the insulation and strength of the coating. But through the test data of comparative example 2, it is added to the coating, due to the reasons of interfacial tension and uneven dispersion, it cannot achieve the expected effect.

[0052] In order to reduce the interfacial tension of boron nitride nanosheets and achieve good dispersibility, the inventors of this application modified the boron nitride nanosheets by alkalizing them so that their surfaces were covered with a large number of hydroxyl groups. They were then grafted with carboxyl-terminated hyperbranched polyesters through an esterification reaction. Double-bond acrylates were then grafted through an esterification reaction and copolymerized with monomers such as styrene and methacrylic acid. The boron nitride nanosheets were then cross-linked and grafted into acrylic resins, greatly reducing the interfacial tension of the boron nitride nanosheets. The surface of the boron nitride nanosheets contained a large number of double-bond acrylates. After the copolymerization reaction, the double-bond acrylates could serve as cross-linking centers, thereby increasing the cross-linking density of the coating and greatly improving the strength of the coating. In addition, the present application uses carboxyl-terminated hyperbranched polyesters. The molecular viscosity of the hyperbranched polymer is extremely low and the volume is relatively large. After being grafted with the boron nitride nanosheets, the dispersibility of the boron nitride nanosheets is excellent. The high content of double-bond molecules at the end of the branched chain of the hyperbranched polymer greatly reduces the interfacial energy of the boron nitride nanosheets with the coating system. In summary, the coating has a stronger integrity, thereby improving the strength of the coating and reducing the flexibility. While linear molecules contain a higher number of carboxyl groups, their molecular viscosity is also higher, resulting in insufficient dispersion of boron nitride nanosheets and insufficient crosslinking during copolymerization, leading to insufficient strength and flexibility in the coating. This is confirmed by the test data from Example 1 and Comparative Examples 1-2.

[0053] By exploring the molecular weight of the carboxyl-terminated hyperbranched polyester, it was found that the overall performance of the coating was better when the molecular weight was 2600. This was verified by the test data of Examples 1-3.

[0054] On this basis, by replacing the filler with a mixture of modified boron nitride nanosheets and mica powder, the mica powder has the advantages of extremely high electrical insulation, acid and alkali corrosion resistance, elasticity, toughness and sliding, heat resistance and sound insulation, and a small thermal expansion coefficient. Replacing a certain amount of modified boron nitride nanosheets with mica powder can maintain the strength of the coating while improving the flexibility of the coating. This can be seen from the test data of Examples 2 and 4. On this basis, by modifying the mica powder and treating its surface with a silane coupling agent with double bonds, on the one hand, the effect of the silane coupling agent can reduce the interfacial tension, and on the other hand, the double bonds contained can participate in the copolymerization reaction; thereby, the mica powder also becomes a cross-linking copolymerization center, and its dispersibility is also improved. The cross-linking effect of the boron nitride nanosheets synergizes with each other, making the coating excellent in strength and flexibility. This can be seen from the test data of Examples 1 and Examples 4-5. In combination with Examples 6-7, the smaller the particle size of the mica powder, the better the comprehensive performance of the coating, but the improvement from 3000 mesh to 6000 mesh is small. Considering the comprehensive economic cost, the particle size of 3000 mesh is the better choice for production.

[0055] This specific embodiment is merely an explanation of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as such modifications are within the scope of the claims of the present invention, they are protected by patent law.

Claims

1. A fireproof insulating coating for new energy batteries, characterized by: The preparation method comprises the following raw materials in parts by weight: 100-140 parts of water-based acrylic resin raw material, 140-150 parts of deionized water, 0.2-0.4 parts of leveling agent, 45-55 parts of ammonium polyphosphate, 0.5-2 parts of film-forming aid, and 0.1-1 parts of defoaming agent. The preparation method of the water-based acrylic resin raw material is as follows: Under a nitrogen atmosphere, using n-butanol as a solvent, adding 6-12 parts by weight of filler, stirring and dispersing, then adding 4-7 parts by weight of styrene, 1-4 parts by weight of methacrylic acid, 3-7 parts by weight of hydroxyethyl acrylate, 3-7 parts by weight of methyl methacrylate, and 15-25 parts by weight of butyl acrylate, stirring until dissolved, then adding 0.2-0.3 parts by weight of dibenzoyl peroxide, raising the temperature to 85-100° C., stirring and reacting; then continuously adding 12-18 parts by weight of styrene, 4-7 parts by weight of methacrylic acid, 8-12 parts by weight of hydroxyethyl acrylate, 8-12 parts by weight of methyl methacrylate, and 30-40 parts by weight of butyl acrylate, stirring until dissolved, continuously adding 0.4-0.6 parts by weight of dibenzoyl peroxide, stirring and reacting, and removing n-butanol to obtain a water-based acrylic resin raw material; The filler comprises modified boron nitride nanosheets, which are prepared by alkalizing boron nitride nanosheets to obtain hydroxylated boron nitride nanosheets, then grafting end-carboxyl hyperbranched polyester through esterification reaction, and then esterifying with hydroxypropyl methacrylate to obtain the filler.

2. A fireproof insulating coating for new energy batteries according to claim 1, characterized in that: The average molecular weight of the carboxyl-terminated hyperbranched polyester is 2600.

3. The fireproof insulating coating for new energy batteries according to claim 1, characterized in that: The boron nitride nanosheets have a diameter of 0.1-0.6 μm, a thickness of 20-80 nm, and a specific surface area of ​​500 m 2 / g.

4. The fireproof insulating coating for new energy batteries according to claim 1, characterized in that: The filler is a mixture of modified boron nitride nanosheets and mica powder, and the weight ratio of the modified boron nitride nanosheets to the mica powder is 5:(0.1-2.5).

5. The fireproof insulating coating for new energy batteries according to claim 4, characterized in that: The mica powder is modified mica powder, which is prepared by reacting mica powder with a silane coupling agent containing double bonds.

6. The fireproof insulating coating for new energy batteries according to claim 5, characterized in that: The double bond-containing silane coupling agent is one or more of vinyl triethoxysilane, vinyl triisopropoxysilane, vinyl tributylanoxime silane, acryloxymethyl trimethoxysilane, 7-octenyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane.

7. The fireproof insulating coating for new energy batteries according to claim 5, characterized in that: The particle size of the mica powder is 3000 mesh.

8. A method for preparing a fireproof insulating coating for new energy batteries according to any one of claims 1 to 7, characterized in that: It includes the following steps: A water-based acrylic resin raw material, deionized water, a leveling agent, ammonium polyphosphate, a film-forming aid and a defoaming agent are stirred and mixed to obtain a fireproof insulating coating for new energy batteries.